2015
DOI: 10.1016/j.arth.2015.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taper Design on Trunnionosis in Metal on Polyethylene Total Hip Arthroplasty

Abstract: Keywords:taper corrosion taper design trunnionosis metal-on-polyethylene total hip arthroplasty This study examines how taper design affects corrosion and fretting at the head trunnion surface. All hip prostheses retrieved between 1999 and 2013 with 28 mm/+0 heads were selected, resulting in 44 cobalt-chrome-onpolyethylene implants, representing six taper designs. Mean implantation time: 8.9 ± 3.7 years. The femoral head tapers were scored for fretting and corrosion using the Goldberg scale as both a combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 29 publications
2
76
0
1
Order By: Relevance
“…10 That corrosion was greatest within the lowest zone of the taper connection also agrees with previous studies of retrieved hip implants with varying taper designs. 12 This lowest zone of the taper experiences torques that could potentially disrupt the oxide passivity film that forms on alloy surfaces and prevents transportation of metal ions, thus preventing oxidation. 13 The lowest zone is also exposed to the oxygen-rich synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 That corrosion was greatest within the lowest zone of the taper connection also agrees with previous studies of retrieved hip implants with varying taper designs. 12 This lowest zone of the taper experiences torques that could potentially disrupt the oxide passivity film that forms on alloy surfaces and prevents transportation of metal ions, thus preventing oxidation. 13 The lowest zone is also exposed to the oxygen-rich synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…First identified with metal-on-metal total hip implants, tribocorrosion in taper junctions has now also been identified in metal-on-plastic total hip implants and in modular total knee replacement. 1,12 Many different factors are thought to be associated with tribocorrosion, including head size, head offset, head angle, flexural rigidity of the neck, dissimilar alloy pairings, and dimensions of the modular taper connection itself. 7 Modularity is also widely used in shoulder arthroplasty implants.…”
mentioning
confidence: 99%
“…15,23 This is also supported by retrieval studies which show that corrosion and fretting scores correlate strongly with increasing head offset (lever arm between the centre of the head and the centre of pressure of the trunnion) and head size. 8,9,24 Even with bearing types other than MoM, studies have reported corrosion and wear at the taper junction, 2,9,13,25,26 with the majority relating to larger head sizes. 2 For example, evidence of significantly increased fretting and corrosion has been seen in 36 mm, compared with 28 mm, heads in metal-on-polyethylene (MoP) bearings.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the trunnion itself may contribute to the development of MACC [22], [23]. The base of shorter trunnions lies within the taper of the femoral head, which may increase edge loading and base corrosion [24] and may increase material wear [25]. The evidence is conflicting regarding taper angle, with one study showing significantly higher fretting scores in 11/13 tapers than those in more narrow type 1 tapers [26], but others show more wear with wider 12/14 tapers than with 11/13 [25].…”
Section: Discussionmentioning
confidence: 99%